Balancing economic growth and environmental conservation through the optimization of rail transit routes for sustainable development - Yinjie He; Xinran Liu; Edward Sun; Dafang Wu (Scientific Reports)
Abstract Drawing from the United Nations Sustainable Development Goals (SDGs), this study offers a framework for optimizing rail transit routes, balancing economic benefits with environmental preservation. Using the Bivariate Choropleth-Multi-Criteria Decision Analysis (BC-MCDA) model, we categorize global regions into economic benefit, environmental conservation, high-conflict, and low-conflict zones. Specifically, 7.42% are identified as economic benefit zones, suitable for rail transit expansion with minimal environmental impact. Meanwhile, 16.14% are environmental conservation zones, requiring preservation and 76% are low-conflict zones, where maintaining existing land use is advised. Only 0.62% are high-conflict zones, demanding careful planning. Addressing how to utilize land more effectively and sustainably in transportation development to foster economic growth while avoiding harm to biodiversity and ecosystems, this study provides actionable insights. It advances sustainable transportation planning by integrating environmental and economic considerations, offering practical guidance for aligning infrastructure projects with global sustainability goals.